Evaluating Industrial Stack Emissions in Dong Thap Province, Vietnam Using AERMOD Model - Quan, Tran Anh; Ngoc, Nguyen Thi Hong (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study employs the AERMOD dispersion model to analyze the spatial and temporal distribution of total suspended particles (TSP), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) from 36 industrial stacks across 19 major plants in Dong Thap province, Vietnam. Using high-resolution meteorological data from 2021-2023 from ERA5 reanalysis dataset, the research examines maximum concentrations, 99 th percentile scenarios, and annual averages. Results indicate that while extreme events can produce localized pollutant concentrations exceeding national standards—with maximum 1-h concentrations reaching 312 µg/m³ for TSP, 373.2 µg/m³ for SO 2 , and 643.4 µg/m³ for NO 2 —these occurrences are infrequent. The 99 th percentile 1-h concentrations (68.8 µg/m³ TSP, 58.8 µg/m³ SO 2 , 101 µg/m³ NO 2 ) and annual averages remain below regulatory limits, suggesting severe pollution events occur less than 1% of the time. Spatial analysis reveals higher pollutant concentrations in southern Dong Thap, particularly Sa Dec and Cao Lanh cities, with rapid dispersion facilitated by the flat terrain. Seasonal variations in pollutant concentrations are evident, with higher levels observed during the dry season compared to the wet season. The study shows the significant influence of seasonal monsoon patterns on pollutant dispersion, with the southwest monsoon (May-October) associated with higher wind speeds and broader pollutant dispersion. This research provides crucial insights for air quality management in rapidly industrializing regions, highlighting the need for targeted mitigation strategies in industrial zones while considering the potential for inter-provincial pollution transport.